Lung function analysis of marble home industry workers in Tulungagung Regency - Widajati, Noeroel; Martiana, Tri; Utami, Tri Niswati; Jalaludin, Juliana; Hamedon, Titi Rahmawati (Universiti Putra Malaysia Press, 2023)
This study analyzes the effect of dust exposure and worker characteristics on lung function. This type of research was observational with a cross-sectional design. The population was 20 marble home industry workers in Tulungagung. The total population technique determined the sample. Data analysis was carried out using Smart PLS software. The study results found that sociodemography, including age, nutritional status, and years of service, affected lung function with a t-statistic of 2.604. Dust exposure, which includes respirable dust content and duration of exposure, impacted lung function with a t-statistic of 2.522. Marble artisans in Tulungagung with the age of >35 years and a long working period of >5 years with a level of exposure to silica dust >3 mg/m3 and supported by a long working period of >7 hours had great potential for lung function. The recommendation was for home industry entrepreneurs to provide masks according to standards. The role of public health center officers was to monitor the work environment and regularly check home industry workers’ health.